1999
DOI: 10.2307/2656820
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in Lupinus (Fabaceae: Papilionoideae) based on internal transcribed spacer sequences (ITS) of nuclear ribosomal DNA

Abstract: Internal transcribed spacer (ITS) sequences of nuclear ribosomal DNA from 44 taxa of the genus Lupinus and five outgroup taxa were used for phylogenetic analysis. Lupinus appears as a strongly supported monophyletic genus, which is unambiguously part of the Genisteae. The lupines are distributed into five main clades in general accordance with their geographical origin. In the Old World, almost all the recognized taxonomic units are well resolved. The ITS data reveal an unexpectedly close relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
102
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 82 publications
12
102
0
Order By: Relevance
“…One hundred forty-eight accessions representing 98 species covering previously recognized Lupinus clades (24), the geographic range, and eight outgroup species representing five genera from tribe Genisteae were sampled. To test the monophyly of the Andean species, 53 accessions representing 36 species were sampled spanning the range of life forms (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…One hundred forty-eight accessions representing 98 species covering previously recognized Lupinus clades (24), the geographic range, and eight outgroup species representing five genera from tribe Genisteae were sampled. To test the monophyly of the Andean species, 53 accessions representing 36 species were sampled spanning the range of life forms (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The vast range of morphological variation (from tiny herbs to large trees) and ecological adaptation (from coastal sand dunes to montane forests) pose challenges for resolving phylogenetic relationships using taxonomic methods (Drummond et al, 2012). Comparisons of nuclear and chloroplast DNA sequences (Ainouche and Bayer, 1999;Wink and Mohamed, 2003;Ainouche et al, 2004;Ree et al, 2004;Drummond and Hamilton, 2007;Drummond, 2008;Eastwood et al, 2008b;Drummond et al, 2012) have made some progress toward resolving Lupinus phylogeny, but ambiguities still remain. Current efforts are underway to sample large gene sets obtained by whole transcriptome sequencing across New World Lupinus (C. Hughes, G. Atchison, D. Filatov, personal communication), which should definitively answer these remaining questions.…”
Section: A Genus Lupinus Lmentioning
confidence: 99%
“…Chromosome numbers range from 2n = 32 to 2n = 52, and nuclear DNA contents range from 2C = 0.97 pg to 2C = 2.44 pg (Naganowska et al, 2003), although rare autopolyploids have been observed with 2n = 100 and 2n = 104 chromosomes (Ainouche and Bayer, 1999). The most strongly supported clade within the Old World lupins is the rough-seeded type, with four less well-defined smooth-seeded sections recognized (Ainouche and Bayer, 1999). Three smooth-seeded Old World species have been used regularly in agriculture: L. albus, as long ago as 2,000 BC; and L. angustifolius and L. luteus by the 19th century (Gladstone, 1970).…”
Section: A Genus Lupinus Lmentioning
confidence: 99%
See 2 more Smart Citations